Epigenomic profiling of primary gastric adenocarcinoma reveals super-enhancer heterogeneity - Wen Fong Ooi (Nature Portfolio, 2016)
Gene expression is regulated by enhancers and super-enhancers, which can be identified by chromatin profiling. Here, the authors surveyed gastric cancer samples and cell lines to identify enhancer elements exhibiting somatic alterations.